Effect of Polyvinylpyrrolidone on Vitrification of Buffalo (Bubalus bubalis) Oocytes - Bari, Jannatul; Islam, M.N.; Alam, Md Hasanur; Khatun, A.; Hashem, M.A.; Moniruzzaman, M. (Journal of Buffalo Science, 2020)
Vitrification, a method of rapid cooling, is an alternate cryopreservation method of oocytes and embryos. The present study was aimed to examine the effect of polyvinylpyrrolidone (PVP) on vitrification of buffalo oocytes. Cumulus oocyte complexes (COCs) with fully grown oocytes (120-130 µm in diameter) were aspirated from slaughtered buffalo ovaries for vitrification. COCs were treated with equilibration solution at room temperature for 5 min and then transferred to a vitrification solution for 1 min. Then the COCs were submerged into liquid nitrogen (-196̊C) for a while using cryotops. The COCs were thawed, diluted, and washed in a washing solution for 5 min, respectively. Vitrified oocytes were incubated for in vitro maturation (IVM) at 38.5̊C under an atmosphere of 5% CO2 in the air for 24 hrs. Cumulus cells surrounding the oocytes were removed mechanically, oocytes were fixed in acetic acid and ethanol, and stained with aceto-orcein to examine the meiotic stages of oocytes. The numbers of morphologically normal oocytes after vitrification were higher in 5% PVP than 0 and 10% PVP groups. A proportion of oocytes treated with 5% PVP reached the metaphase II (MII) stage while none of the oocytes from 0% and 10% PVP groupsdeveloped beyond anaphase I and metaphase I (MI) stages, respectively. These results show that PVP can be used as a cryoprotectant for the vitrification of buffalo oocytes.